2020
DOI: 10.3390/su12208633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Padel Match on Biochemical and Haematological Parameters in Professional Players with Regard to Gender-Related Differences

Abstract: Haematological and biochemical parameters have not yet been analysed in professional padel players. The aim of this study was to determine the basal values of these parameters and to observe the effect of a simulated competition on them, including gender-related differences. A total of 14 male professional players (age: 28.2 ± 7.9 years), and 16 female professional players (age: 29.7 ± 3.7 years) participated in this study. Players were allowed to hydrate ad libitum during the matches. Haematological and bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 52 publications
8
26
3
5
Order By: Relevance
“…However, RPT did not show any differences between groups. While these sex-related effects were in accordance with the findings of a very recent study [ 4 ], they were contrary to those reported by Torres-Luque et al [ 24 ], who found higher TPT and RPT in female players. In any case, TPT in our study was established approximately between 55 and 80 min, which is in line with these previous reports.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, RPT did not show any differences between groups. While these sex-related effects were in accordance with the findings of a very recent study [ 4 ], they were contrary to those reported by Torres-Luque et al [ 24 ], who found higher TPT and RPT in female players. In any case, TPT in our study was established approximately between 55 and 80 min, which is in line with these previous reports.…”
Section: Discussionsupporting
confidence: 78%
“…Our results are similar to those previously described by Castillo-Rodriguez et al [ 1 ], who reported a HR mean equivalent to 77% of HR max during padel competition. Only one previous study [ 4 ] has considered the impact of padel practice on the hemodynamic variables that could modulate other physiological and/or biochemical responses in padel players. Accordingly, it seems necessary to check PV changes associated with intense outdoor exercise, especially if athletes need to hydrate to replace the water lost through sweating and to maintain an adequate thermoregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding its game dynamics, during rallies, padel combines short, highly intensive actions (0.7–1.5 s) and other longer, less intensive actions (9–15 s), which are alternated with pauses and rests between points that normally last 10–20 s [ 7 ]. Padel is characterized by being an intermittent sport that is predominantly aerobic and one that includes short high-intense and very high-intense game actions, during which the phosphagen system prevails (ATP-PCr) [ 8 , 9 , 10 ]. Indeed, low-intensity and rest periods occupy around 60% of playing time [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…During a padel match, players have to perform rapid movements and constantly change direction in very short times. This means that strength, agility, and speed are important physical qualities to play this sport [ 10 ]. Compared to other racket sports, padel’s characteristics have drawn more researchers’ interest in recent years [ 4 , 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%